Patterns and characteristics of injuries encountered in road traffic accidents and effect of pre-hospital care on their outcome: a tertiary-hospital study in Lahore, Pakistan - Ikram, Maryam; Fatima, Rida; Ikram, Anam; Shahid, Farheen; Rafiq, Maham; Nisar, Tooba (International Journal Of Community Medicine And Public Health, 2019)
Background: Road traffic accidents are the eighth leading cause of death worldwide, contributing significantly to the global disease burden. As there is a paucity of published data on RTAs in Lahore, this study was carried out to highlight injuries encountered in RTA victims and provide baseline data for the establishment of prevention strategies in our locality. Methods: This is a descriptive cross-sectional study of RTA victims admitted in Mayo Hospital, Lahore to determine factors associated with RTAs, characteristics, and outcomes of injuries sustained and effect of Pre-hospital care in determining the outcome. Results: Out of total 100 subjects recruited, 89 were males and 11 females. Ages of patients ranged from 5 to 70 years with the most injured age group ranging between 11-30 years (59%). Motorcyclists were found as the most vulnerable road user group (61%). Most of the accidents occurred because of a collision with another vehicle (45%). 65 victims received pre-hospital care en route to Mayo Hospital, which was found effective in preventing major disabilities in 81% of cases (53 out of 65). Incidence of Musculoskeletal injuries was highest (55%). Most patients (86%) were discharged without permanent disabilities. No patient died during our study. Conclusions: This study shows road traffic accident is a major public health problem in our setting and contribute markedly to high morbidity. Urgent preventive measures should be established to reduce the risk of their occurrence. Early recognition and prompt treatment are important for the survival of the victims.